Unicorn (Rowan Tree Church) [5], [no. 1] (Hallow 1981) - Beyerl, Paul, Rev. (Rowan Tree Church Periodicals Collection, New Age Movements, Occultism, and Spiritualism Research Library. Archives and Special Collections, 2020, 1981)
Uniblessins / Adrius -- Unicorn Chronicles, cont. / Rev Paul V. beyerl, D.D. -- Happenings -- We all come from the Goddess / art by Zora -- Notes from an Herbal -- Guinevere the Shimmering / Gawain Ross -- Journeys / Noel-Anne Brennan -- Lifelight & Shadows / Prairie Jackson -- Publications -- Letters from Readers -- Childrens Corner: A Green Hobgoblin / Florence Page Jaques -- [Unicorn Astrologer] / art by K.L. Weed -- [Boy] / art by Joshua 6 -- Three Little Witches / Marjorie Barrows -- My Darling, Precious Andrius / Unibella -- Meriah / J. Baker -- Deer Friends / Flowers -- [Announcement form Good Fairy Productions] -- Reader Poll concerning Extra Pages
1 Electronic record(s) and derivatives. 8760412 bytes. 21 pages.
Keywords: Rowan Tree Church; Saturn (Planet); Beyerl, Paul V., Rev., 1945-; Bartlett, Judy; Horoscopes; Alchemilla; Guenevere, Queen (Legendary character)--Poetry; Daydreaming--Poetry; Shadows--Poetry; Goblins--Poetry; Poetry--Child authors; Art--Child artists; Juvenile witches--Poetry; Andrius (Fictitious character)--Poetry; Meriah (Cat)--Poetry; Cats--Poetry; Murphy, Charlie. Catch the fire; Baumli, Francis, 1948- Men freeing men; Poetry; Questionnaires; Newsletters